EVALUATION OF PIGEONPEA GERMPLASM LINES FOR RESISTANCE AGAINST FUSARIUM WILT DISEASE INCITED BY FUSARIUM UDUM - C. SUDHAKAR and C. SUDHA RANI, T. RAJESHWAR REDDY, B. VIDYASAGAR, S. SANDEEP, G. UMA DEVI, S.N.C.V.L. PUSHPAVALLI, G. SRIDEVI (The Journal of Research, PJTSAU, 2023)
A study was conducted to evaluate one hundred and seventy two pigeonpea germplasm lines against fusarium wilt in wilt sick plot during Kharif 2019-20 and Kharif 2020-21 at Agriculture Research Station, Tandur. This experiment was laid out in randomized block design with two replications, wherein checks of ICP 2376 (Susceptible check) and ICPL 87119 (Resistant check) were planted after every five rows of the germplasm lines to ascertain the uniformity in disease incidence across the sick plot. Significant differences in disease incidence among pigeonpea germplasm lines were observed in both the years of screening. Based on disease reaction, the per cent disease incidence (PDI) was calculated and the germplasm lines were divided into one of three categories i.e., Resistant (R), Moderately Resistant (MR) and Susceptible (S). The pooled analysis of consecutive two years viz., Kharif, 2019-20 and Kharif, 2020-21 revealed that, out of 172 germplasm lines, 21 germplasm lines showed resistant reaction with 0-10% disease incidence, of which six lines were asymptomatic in expression. While, remaining 45 germplasm lines exhibited moderately resistant in reaction, with 11-30 per cent disease incidence. The other 106 germplasm lines showed susceptible reaction with incidence that was greater than 30 per cent.